Sea la Luz - Martinez, Juan Francisco (University of North Texas Press, 2006)
Mexican Protestantism was born in the encounter between Mexican Catholics and Anglo American Protestants, after the United States ventured into the Southwest and wrested territory from Mexico in the early nineteenth century. Sea la Luz tells the story of Mexican converts and the churches they developed through the records of Protestant missionaries. Juan Francisco Martinez traces Protestant mission work among the Spanish speaking of the Southwest throughout the nineteenth century. By 1900, about 150 Spanish-speaking Protestant churches with more than five thousand adult members existed in the region. They were rejected by their own people because they were Protestants, but Anglo American Protestants did not readily accept them either because they were Mexican. In spite of the pressures from both their own community and the larger society, they forged a new religious identity in the midst of conquest.